SERUM HOMOCYSTEINE CONCENTRATIONS IN PATIENTS WITH HYPERTENSION - Atif, Alina; Rizvi, Muhammadi Atif; Tauheed, Shoaib; Aamir, Irum; Majeed, Farrukh; Siddiqui, Khalid; Khan, Sadaf (Pakistan Journal of Physiology, 2008)
Elevated plasma homocysteine is a known risk factor for atherosclerotic vascular disease. In fact, it is an independent risk factor similar to smoking or hyperlipidemia but it is under recognized among the doctors of Pakistan. An elevated homocysteine level induces thrombogenicity, causes procoagulant state and promotes the proliferation of smooth muscle cells. This study was carried out to find out the serum homocysteine levels in patients with known hypertension. Methods: One hundred patients more than 60 years of age of both the sexes with documented hypertension were selected from medical wards and cardiology ward of Civil Hospital Karachi. Study subjects had no history of atherosclerotic disease or diabetes mellitus. Homocysteine estimation was done by FPIA method on IMX. Results: It was seen that 80% patients selected had an elevated homocysteine levels (18.77Â±1.9 as against 5â€“15 taken as normal). Conclusion: We have observed that serum homocysteine is raised in most of the patients with hypertension.